Role of multi detector computed tomography (MDCT) in evaluation of renal masses - Karthikeyan, M. A.; Vohra, Poonam (International Journal of Research in Medical Sciences, 2018)
Background: Due to rapid pace in development of imaging techniques and increasing number of investigations being done, more number of renal masses are discovered incidentally during evaluation of unrelated or unspecific symptoms. Hence it is vital to differentiate neoplastic and non-neoplastic masses. Among the neoplastic masses, there is a need to differentiate benign and malignant masses so that appropriate treatment strategies like nephron sparing surgery, radio frequency ablation etc. can be planned at an early stage and avoiding unnecessary radical treatments for improved patients survival. Methods: A Cross-sectional Observational study was done in 35 patients. Patients of either sex in any age group who had presented with suspected renal mass by clinical signs and symptoms (palpable renal angle mass, renal angle pain, hematuria) confirmed on USG examination or an incidental Renal mass diagnosed on USG/CT examination were included in our study. Results: Ultrasound is the initial imaging modality of choice since it is inexpensive, easy to perform and no radiation exposure. On USG, the renal lesions are classified as solid or cystic. Anechoic, thin walled cyst without any septations or solid components is usually Bosniak I cyst (simple cyst) and does not need any further evaluation. Rest of the cystic and solid lesions cannot be characterized by ultrasound and hence need further evaluation. Conclusions: Multidetector Computed Tomography is the imaging modality of choice for further evaluation and characterization. CT is done in four phases viz., unenhanced, corticomedullary, nephrographic and excretory phase especially in cases of malignancy while in benign conditions like angiomyolipoma and abscess, evaluation with unenhanced and single phase post contrast in portovenous phase is sufficient.